Effectiveness of micronized progesterone for the prevention of miscarriage - L I Maltseva; D M Nikogosyan (IP Berlin A.V., 2015)
The data on the efficacy of micronized progesterone (Prajisun) for the prevention of miscarriage in women with a obstetric and gynecological history. Materials and methods. The study involved 56 women aged 19-38 years at 4-14 weeks of pregnancy, of which the main group of 30 were: infertility in anamnesis - 17 thrombophilic states against the background of the centers of urogenital infection - 7, uterine malformations - 6 pregnant. A control group comprised 26 healthy women without a history of complications during current pregnancy. All patients have gone through the physical examination, including the definition of the parameters of hemostasis D-dimer, AIII, protein C and S. In the study, blood levels of progesterone, interleukin-1b, interferon-y before and after treatment with micronized progesterone. Changes in the hemostatic system is also evaluated in the dynamics of observation and treatment.The results of the study. Among women, in the main group lower levels of progesterone in the blood were found, with the most pronounced case being retrochorial hematoma. The threat of abortion directly correlated with the level of progesterone and content of proinflammatory cytokines in the blood, the values of which are several times higher than health indicators: , interleukin-1b - 5, interferon-y - 3,7 times. Against the background of treatment with 400 mg Prajisun vaginally within two weeks there was a significant decline in pro-inflammatory cytokines, increased progesterone levels, normal levels of fibrinogen, D-dimer and spontaneous rate of platelet aggregation. Pregnancy progressed successfully in all women.Conclusion. The use of micronized progesterone Prajisun in early pregnancy in women with obstetric and gynecological history pathogenetically substantiated and effective in reducing high risk of miscarriage.